Samuel's choice - Berleth, Richard; Watling, James (New York : Scholastic, 1990)
Samuel, a fourteen year-old slave in Brooklyn in 1776, faces a difficult choice when the fighting between the British and the colonists reaches his doorstep and only he can help the rebels.
Keywords: African american -- Fiction; United State -- 1775-1783 -- History Revolution -- Fiction